Environmental hypocrisy (in a nutshell) (Revista do Tribunal Regional Federal da 3ª Região, 2010)
We hear every day, all the time, and - why not say it - with irritating insistence, that we are moving at a rapid pace (and for the more pessimistic, irreversibly) towards removing the planet from the exceptional environmental stability in which it has been for more than 10,000 years, with consequences that are simply unthinkable. Although there is no denying the relative veracity of the authentic “general warning” that is constantly being issued, particularly by the media - including the persistent news about the disruption of the balance of three of the nine “planetary thresholds” (climate change, the loss of biodiversity and the alteration of the nitrogen cycle) - there is still an authentic and regrettable conspiracy, on the part of politicians and, to some extent, also on the part of the main scholars on the subject, in the sense that the definitive solution to the problem must be based on the synergistic fight against the effects of the aforementioned environmental imbroglio and not properly on the primary causes that lead (and have historically led) to its origin, which is continuous and uncontrolled population growth, especially in underdeveloped countries.
Keywords: environmental law; population control; life expectancy; global warming